History of the plyometric training: A review in sport - Marques Junior, Nelson Kautzner (Tanjungpura Journal of Coaching Research, 2025)
Background and Study Aim. From 1919 to 1930, the athletics coaches prescribed the first sessions of plyometric training for their athletes in Nothern and Eastern Europe. The objective of the review was to present the history of the development of plyometric training.Material and Methods. This study followed the methodology proposed by PRISMA statement (Moher et al., 2009). The articles were selected from January to September of 2024 in 10 databases (Google Scholar, PubMed, Research Gate, Scielo, Redalyc, Scopus, DOAJ, ScienceDirect, Semantic Scholar, and Latindex) with the following keywords: (“plyometric training” AND “stretch-shortening cycle” AND “sportive strength training”). The articles were selected from January to September of 2024 in 10 databases. The printed books the author used in your library and the printed articles were sent by e-mail to the author by his Italian friend G. B.Results. Plyometric training has three historical moments. The empirical period was of the ancient people until the year 60, the moment that the coaches prescribed the plyometric training based on observation of the sessions. The scientific period was from 1960 to 1999, the moment that occurred in the technological evolution of exercise physiology and biomechanics laboratories, this allowed sports scientists to conduct research with plyometric training. The modern period was from 2000 until the present day, the moment that the scientists need to study some questions this training.Conclusion. In conclusion, plyometric training is a strength training practiced by most high-performance athletes because increases explosive and reactive strength which are important for various sports.